The role of social entrepreneurship for youth purpose development. Issue 2 (4th May 2021) - Ong, Dalphine; Shang, Liang; Chandra, Yanto; Hamidi, Mashitah; Wahab, Haris Abd
ABSTRACT: Despite the burgeoning research on social entrepreneurship in recent years, there is limited research on youths as a context for theorizing. This article examines the influence of social entrepreneurship on youth development through the positive youth development perspective. It explores how youth participation in social entrepreneurial activities helps develop their sense of purpose in life. Using data from semi-structured interviews with 27 youths and participant observations, this article demonstrated that social entrepreneurship contributes to youth purpose development by facilitating social conscience, prosocial connectedness, capability and personal agency development and how these manifest in different stages of youth purpose commitment.